Abnormal Serum Iron-Status Indicator Changes in Amyotrophic Lateral Sclerosis (ALS) Patients: A Meta-Analysis - Wang, Lan; Li, Chunyu; Chen, Xueping; Li, Shuying; Shang, Huifang (Frontiers in Neurology, 2020)
Background: In recent years, the role of iron metabolism in amyotrophic lateral sclerosis (ALS) arises more and more attention, and some studies have focused on the link between abnormal serum iron indicators and ALS. But there are still big conflicts and inconsistency among different studies. To study the possible relationship between amyotrophic lateral sclerosis (ALS) and disturbed iron metabolism, we conducted this meta-analysis to conclude characteristics of abnormal serum iron-status indicators changes in ALS patients. Methods: We searched and screened main databases, including the PubMed, Embase and Cochrane Library, to find studies related to the association between iron metabolism and ALS. The Revman 5.3 software was used to conduct meta-analysis. Results: Eleven studies were finally included in our analysis, composing of 1599 ALS patients and 1255 controls in total. The results showed that the ferritin level was much higher in ALS patients compared with controls (MD=70.48, 95%CI [51.41,89.55], p<0.00001), and the transferrin level was decreased in ALS patients compared with controls (SMD=-0.28, 95% CI [-0.38,-0.18], p<0.00001), while there was no statistical difference in iron levels (SMD=0.48, 95% CI [-0.07,1.03], p=0.09) between ALS patients and controls. Conclusions: Our research finds unusual changes in several indicators representing iron-status, which suggest possible iron metabolism abnormalities in ALS patients. That may provide evidence for the link between iron metabolism and the pathogenesis of amyotrophic lateral sclerosis.